2021
DOI: 10.1007/s43032-021-00493-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Semen IL-6, IL-33 and Malondialdehyde Generation in Human Seminal Plasma and Spermatozoa

Abstract: Cytokines are physiological seminal components and their abnormal levels, reported in different pathological conditions, negatively influence the sperm function. We analysed the relationship between interleukin (IL)-6 and IL-33 levels and lipid peroxidation (LPO), measured both in semen and sperm lysate, in 44 human semen samples. The semen analysis was performed following the WHO guidelines. Seminal IL-6 and IL-33 concentrations were assessed by ELISA and LPO was evaluated measuring malondialdehyde (MDA) both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Cytokines are physiological seminal components, and their abnormal levels, reported in different pathological conditions, disrupt semen function. 47 Many so-called proinflammatory and immunoregulatory cytokines are produced by testicular somatic and spermatogenic cells, both under normal conditions and in response to inflammatory stimuli. 48 Seminal cytokines are also secreted by immunocompetent cells in various pathogenic conditions, including leukocytospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are physiological seminal components, and their abnormal levels, reported in different pathological conditions, disrupt semen function. 47 Many so-called proinflammatory and immunoregulatory cytokines are produced by testicular somatic and spermatogenic cells, both under normal conditions and in response to inflammatory stimuli. 48 Seminal cytokines are also secreted by immunocompetent cells in various pathogenic conditions, including leukocytospermia.…”
Section: Discussionmentioning
confidence: 99%
“…showed a positive correlation between IL-6 levels and the level of malondialdehyde (MDA) in semen. The levels of malondialdehyde(MDA) in seminal plasma and semen were negatively correlated with sperm parameters, which further confirmed that IL-6 was involved in oxidative stress induced sperm damage ( 28 ). IL-1α and IL-1β are two forms of IL-1, which are regulators of testicular function, but increased expression of IL-1α and IL-1β in rats with varicocelectic veins, especially in the 11 - and 13-week-old groups, disrupted the balance of inflammation and immunity and had deleterious effects on testicular tissue ( 15 ).…”
Section: Varicocelementioning
confidence: 66%
“…IL23 was detected using ELISA technology in two studies, published in 2011 and 2014, and comprising 45 normozoospermic and fertile men (Table 1) at median and mean concentration of 5.9 and 2.2 pg/mL, respectively 75,80 (Figure S2E). IL33 was reported to be undetectable by ELISA in SP from 11 men in a single study published in 2021, including in men with varicocoele and genital infections 112 (Figure S2F, Table 1). One study, published in 2017, reported SP IL37 concentration to be significantly higher in infertile men with varicocoele, compared to healthy fertile men 111 .…”
Section: Resultsmentioning
confidence: 99%
“…IL33 was reported to be undetectable by ELISA in SP from 11 men in a single study published in 2021, including in men with varicocoele and genital infections 112 (Figure S2F, Table 1). One study, published in 2017, reported SP IL37 concentration to be significantly higher in infertile men with varicocoele, compared to healthy fertile men.…”
Section: Ilsmentioning
confidence: 98%